INDEPENDENTLY RUNNING TRAINING MODEL ON LIMITED BOX AREA FOR ATHLETES WITH VISUAL IMPAIRMENT CLASSIFICATION TOTAL BLINDNESS - Slamet Widodo; Tandiyo Rahayu Rahayu; Furqon Hidayatullah; Setya Rahayu (Journal of Physical Education and Sports, 2026)
This study aims to examine (1) Exercise models in a limited box area that can be used for independently running training for athletes with visual impairments classified as totally blind. (2) The acceptance and implementation of the training model in a limited box area for independently running training for athletes with visual impairments classified as totally blind. The method used in this study is development research. Outline the steps for the development of the model in 4 stages, namely: (1) Preliminary research; (2) Model development planning; (3) Validation, evaluation, and revision of the model; and (4) Model implementation. In the process of developing the model, 2 test stages were carried out, namely 1 time in a small group and 1 time in a large group. The data in this study is a combination of quantitative and qualitative data. After this study, it was concluded that (1) the form of a training model in a limited box area that is barrier-free, safe, and comfortable can be used for athletes with visual impairment classification of total blindness for independently running training. (2) The training model in a limited box area can be accepted and used to carry out independently running training for athletes with visual impairments classified as totally blind, with an acceptance and implementation rate of 92.86%.